A British education control officer in occupied Germany, 1945-1949 - Phillips, David, 1944 December 15- author.
1 online resource.
Keywords: "Edward Aitken-Davies (1899-1981) served as an Education Control Officer in the British Zone of occupied Germany from the early summer of 1945 until December 1949. He thus experienced the implementation of policy in the Zone from the very beginnings of the occupation until the founding of the Federal Republic of Germany in 1949. During the period 1945 to 1947 he wrote weekly letters home to his mother. Those letters, together with the many speeches he gave in Germany during his time as a leading British officer in the Hanover region have not hitherto been available to researchers but can now be made accessible in edited form. The letters are placed in the context of developments in British policy and with explanatory notes on the detail. Taken together, his letters and other documents provide insights into the day-to-day lives of the impressive group of individuals who oversaw the development of education in Germany from post-war chaos to the reform and stability which restored the education system of the country to a pre-eminent status in Europe"--